Assessment of Phenotype Characteristics of Fetal Neural Cells after Cryopreservation Using Different Freezing Regimens - Porozhan, Ye. A.; Ostankov, M. V.; Babenko, N. N.; Goltsev, A. N. (Problems of Cryobiology and Cryomedicine, 2024)
In the paper the effect of three different cryopreservation regimens on subpopulation composition of fetal neural cells (FNCs) of 11 gestation days was analyzed. FNC subpopulations revealed different sensitivity to the effect of physical and chemical factors of cryopreservation, implemented when using these freezing regimens. The fact of higher cryostability of glial and stem cells in biomaterial of heterogenous composition independently on freezing regimen was found. It has been shown that using one of the regimens in general pool of FNCs the number of multipotent progenitor cells with CD133 and nestin phenotype increases due to the death of more differentiated neuron precursors. Selective effect of certain cryopreservation regimens on heterogenous content of FNCs was proved.